Analisis Kestabilan Lubang Bukaan dan Pillar saat Proses Mining Blok Development pada Penambangan Bawah Tanah Metoda Room and Pillar PT. Allied Indo Coal (AIC) Jaya - Alfi Rahman; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. Determination of the mining geometry in the room and pillar underground mining method is a fairly complex job. This research was conducted by analyzing the stress on the coal pillar and the coal pillar strength to obtain its safety faktor. Stress determination on the pillars is calculated based on the theory of tributary area loading with the stress working on the pillars is 6.775 MPa. Meanwhile, the coal pillar strength is obtained using empirical equations with the pillar strength of 17.6 MPa. Thus, the pillar safety faktor based on analytical calculations is 2.62 (stable) with mining recovery around 40%. Rock mass characterization is carried out based on rock mass classification Rock Mass Rating (RMR) System. The value of the RMR for coal is 56, where this rock is included in class III rock with a stand up time recommendation for 580 hours and maximum span 6.5 m. Modeling using Phase2 shows the direction of stress transfer tends to be centered on the mining blok area with average mean stress 4.2 MPa and strength factor 2.53. Evaluation of mining geometry is obtained through simulation calculations for several pillar sizes with the results in the form of recommendations for the ideal pillar dimensions 7 m x 7 m with estimated recovery around 55% and safety faktor 1.53.Keywords:  Pillar Dimensions, Tributary Area, Safety Faktor, Recovery, RMR System